2008
DOI: 10.1007/s00259-007-0661-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of 201Thallium-SPECT and 18F-FDG-PET in the clinical assessment of glioma recurrence

Abstract: FDG-PET does not clearly improve the diagnostic accuracy of (201)Tl-SPECT, which appears to be a more appropriate examination for the diagnosis of possible brain tumour recurrence, especially for ruling it out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…When considering both low-and high-grade gliomas, [16][17][18][19][21][22][23]27,32,33,40,41 sensitivity ranged between 0.23 and 0.95 and specificity ranged between 0.17 and 1.0. For high-grade gliomas, [16][17][18][19]27,34,35,39,41 sensitivity ranged between 0.18 and 1.00 and specificity ranged 0.25 and 1.0. Studies including both low-and high-grade gliomas had a summary sensitivity of 0.77 (95% CI, 0.66 -0.85) and a summary specificity of 0.78 (95% CI, 0.54 -0.91), corresponding to a positive likelihood ratio of 3.4 (95% CI, 1.6 -7.5) and a negative likelihood ratio of 0.30 (95% CI, 0.21-0.43) (Fig 2).…”
Section: Sensitivity Specificity Likelihood Ratios and Summary Rocmentioning
confidence: 99%
“…When considering both low-and high-grade gliomas, [16][17][18][19][21][22][23]27,32,33,40,41 sensitivity ranged between 0.23 and 0.95 and specificity ranged between 0.17 and 1.0. For high-grade gliomas, [16][17][18][19]27,34,35,39,41 sensitivity ranged between 0.18 and 1.00 and specificity ranged 0.25 and 1.0. Studies including both low-and high-grade gliomas had a summary sensitivity of 0.77 (95% CI, 0.66 -0.85) and a summary specificity of 0.78 (95% CI, 0.54 -0.91), corresponding to a positive likelihood ratio of 3.4 (95% CI, 1.6 -7.5) and a negative likelihood ratio of 0.30 (95% CI, 0.21-0.43) (Fig 2).…”
Section: Sensitivity Specificity Likelihood Ratios and Summary Rocmentioning
confidence: 99%
“…& Differences in glucose metabolism between tumor and treatment necrosis have been demonstrated on flurodeoxyglucose positron emission tomography (FDG-PET) [57,58], although the diagnostic accuracy for differentiating tumor from necrosis is limited due to the high background uptake and lower imaging resolution. Amino acid radiotracers have the advantage of high lesion to background contrast due to their selective uptake by proliferating tumor tissues.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Diagnosis of brain tumor recurrence has been an imaging challenge also for PET. Although initial reports for 18 F-FDG were encouraging (Di Chiro et al, 1988), more recent studies questioned its diagnostic accuracy, which was found considerably inferior to that of 201 Tl SPECT in several series (Kahn et al, 1994;Gómez-Río et al, 2008). A significant disadvantage of 18 F-FDG derives from its physiological uptake in the glucose-metabolizing normal brain.…”
Section: Other Metabolic Imaging Modalities: Petmentioning
confidence: 99%